Comparison of Linear Multiple Regression Models for the Factors Influencing the Exchange Rate Change in BELL Countries - Tetiana Вludova, Svitlana Usherenko, Olena Horokhova, Тetiana Frolova, Zoriana Lutsyshyn (International Journal of Advanced Science and Technology, 2020)
We investigate theoretical foundations and applications of linear multiple regression models based on the impact of the GDP deflator, chain gains in inflation, import-to-GDP growth in the chain, chain gains in the ratio of FDI to GDP, the chain gains in the ratio of portfolio investments to International Bank for Reconstruction and Development loans, the chain gains of the International Monetary Fund of the Regional Banks financing to portfolio investments at the rate of increase of the exchange rate against the dollar for Bulgaria, Estonia, Latvia and Lithuania, or BELL. We then compare the effects of the components of the exchange rate against the dollar in the selected group of countries